The mediating role of innovation between corporate governance and firm financial performance: evidence from Pakistan - Akram, Farheen (2018)
Although laws concerning the corporate governance have been formulated and also promulgated in Pakistan, yet the Taj Company, Crescent Bank, Mehran Bank and various other firms have emerged a glaring violation of such laws in Pakistan. The previous literature has also highlighted several issues related to the corporate governance among the Pakistani firms, Therefore, the objective of the current study was to investigate the relationship between the corporate governance and performance of the Pakistani firms. In the current study, corporate governance includes board structure (independent directors, foreign directors, board size, gender diversity), board capital (director's education, prestigious education, role legitimacy, directors' interlocks) and ownership structure (concentrated ownership, family ownership, foreign ownership). Besides, this study aimed to investigate the mediating role of innovation between the corporate governance and firm performance to bridge the gap in the existing literature. The theoretical foundation of the current study was based on the agency and resource dependence theories. For this purpose, the data was collected from 188 non-financial firms listed in Pakistan Stock Exchange for the period of 2010-2016. The present study utilized regression with ordinary least square method to achieve the research objectives. The findings revealed that the foreign directors, board size, female' directors, directors' education, prestigious education and directors' interlocks as well as concentrated ownership, foreign ownership and family ownership have significant relationship with firm performance. However, the direct effect of independent directors on firm performance its not' significant. Meanwhile, the findings also showned that innovation mediates the relationship of independent directors and foreign directors, board size, female directors, director's education, prestigious education as well as concentrated ownership and foreign ownership on firm performance, except directors' interlocks and family ownership. Based on the empirical results the current study also suggested that Pakistani firms should invest in innovation to increase their performance.